Interview of John Hobbie Roscoe by Brian Shoemaker - Roscoe, John Hobbie, 1919- (Byrd Polar Research Center Archival Program, 2007)
Apfel, Earl, geologist, p. 51 Behrendt, John, member of IGY expedition, p. 55 Butters, [?], Captain USMC, pp. 63-64 Byrd, Admiral Richard, mentioned throughout Byrd, Richard, Jr. pp. 86-87 Chaney, [?], Admiral Byrd’s Chief of Staff, p. 36 Cox, Charles, p. 18 Cruzen, Richard, Admiral USN, p. 12 Darlington, Jenny, pp. 55-56 Dater, Henry “Harry”, pp. 74, 76-77, 91-92 Dufek, Admiral George, p. 88 Frazier, [?], deputy commander on the Burton Island, pp. 51, 53 Fuchs, Bunny, p. 110 Gooderham, pp. 12-13 Gould, Lawrence, Antarctic explorer, p. 65 Hillary, Sir Edmund, p. 111 Howard, August “Art”, founder of the American Polar Society, pp. 28, 112-14 Ketchum, Hank, commander of the icebreaker Burton Island, pp. 51, 53 Law, Phil, pp. 102-03 Lyon, Waldo, pp. 18-19 Mawson, Douglas, Australian polar explorer, pp. 101-02 Pearson, Drew, Newspaper columnist, pp. 45, 64 Peterson, Pete, physicist, pp. 55-56, 68-69 Quackenbush, Robert, Rear Admiral USN, p. 12 Ronne, Finn, explorer, pp. 54, 68 Ronne, Edith “Jackie,” wife of Finn, pp. 54-55 Shinn, Gus, pilot, pp 41-42 Shirley, Charles, chief photographer, p. 15 Siple, Paul, geographer, pp. 26, 36-37, 74, 76-77, 88, 112 Siple, Ruth, pp. 26-27 Sullivan, Walter, science writer, pp. 23, 25 Victor, Paul Emile, French pilot and explorer, pp. 75-76 Weir, [?], Major, pilot, pp. 35, 37, 64 Wilkins, Sir Hubert, polar explorer, pp. 19, 102 John Roscoe, born in 1919, received an excellent education at Flushing High School in Syracuse, New York. He graduated from Syracuse University in 1940, and in 1941 earned a Master’s Degree there in Geography under George Cressy. His plans for pursuing a Ph.D. at UCLA in the field of cartography, with an emphasis on aerial photogrammetry and photo interpretation, were interrupted when he was urgently recruited to join the Intelligence Office for the Army Air Corps. He remained there until the spring of 1943 working as an interpreter of aerial photographs. He also wrote the manual for aerial photo interpretation, and was one of the very first persons to see the aerial photographs of damage to Pearl Harbor and Wake Island. In 1943 he was called to active military service as a Lieutenant in the Marine Corps. He continued his work as a photo interpreter at the Naval Photo Intelligence School. Later he was assigned to the European theatre of operations. He interpreted through aerial photographs the success of bombing raids in Germany, and he believed his team achieved a 99% success rate in interpretation. Soon after the war ended, Roscoe accepted an Associate Professorship in the Department of Geography at the University of Georgia, but before the first semester ended he was recalled to active duty. He was ordered to join Task Force 68 already on its way to Antarctica. He joined up with Admirals Byrd and Quackenbush in Panama. Roscoe was the only qualified photo interpreter on the expedition, named Operation Highjump. Byrd hoped to photomap as much of Antarctica as he could. Roscoe traveled aboard the command ship, the Mount Olympus, one of thirteen ships in the 5,000 man expedition. As they approached Antarctica they discovered that several hundred miles of the Ross Sea were completely blocked with solid floe ice. The submarine, the USS Stennet, was so badly damaged by ice that it had to return to Panama for repairs. The only two icebreakers on the expedition left temporarily to free the Stennet, and several ships, including the Mount Olympus were locked fast in the ice. Eventually all ships made it safely to an area of open water in the Ross Sea. Admiral Byrd flew into the base at Little America on the first plane. At the time, Byrd was at an advanced age, not well, retired from active service, and had no command. The two icebreakers, the USS Northwind, and the USS Edisto, had rejoined the expedition. Roscoe was a member of the initial landing party, a reconnaissance team, as it entered the abandoned base at Little America, established earlier by Byrd in 1939. The Seabees came next and carved a road through the ice ridges. Soon a tent camp was built, with five rows of ten four-man tents each. Each had a small pot bellied stove in the center. The mess hall was off to one side, and the airfield one-half mile away. Roscoe’s tent mates were Major Weir and Richard Byrd, Jr. Weir was head of the Marines that were flying. The Marines had two R4D aircraft; the Navy had four. One of the great difficulties in getting aerial films was because of the magnetic situation so close to the Pole it was difficult to interpret flight directions accurately. The compasses were off on the planes. For safety reasons two R4D aircraft flew together on photographic flights so that if one of them went down, the other could radio for a search team. All of the R4Ds and the American Mariners, flying boats, had trimetrigon film and camera settings. Another plane used to photograph wildlife and glacial formations was the OY-1, a small, single-engine aircraft. Admiral Byrd consulted Colonel Roscoe about planning photographic flights, and interpreting the films later on. Some twelve correspondents, representing radio networks and national newspapers, were on the mission. Although the relationship between Byrd and Roscoe was tumultuous at times, on the trip home at the end of the expedition, Byrd named Roscoe his envoy to the Prime Minister of New Zealand. Roscoe,along with the twelve correspondents, were all given an extensive tour of New Zealand. The expedition continued on to the United States. After the conclusion of Operation Highjump, Roscoe left the service, and worked in Navy Intelligence as a civilian. He worked for a time as the Navy representative to a military working group, the genesis of what in 1949 would become the Joint Staff of the military branches. Later he agreed to work as the Air Force representative on this committee. Roscoe returned to Antarctica the following year as a member of Operation Windmill, to map “control points.” These were needed to make accurate maps, and were points for which the exact latitude, longitude, and elevation had been determined. Two icebreakers, the Burton Island and the Edisto made the trip. Roscoe represented Naval Intelligence, but he went as a civilian. His principal responsibility was to interpret aerial photographs. He also constructed cairns holding metal claims markers (claiming certain territories for the United States) at various points along the coast, including Haswell Island, a penguin rookery, McMurdo Sound, and Victoria Land. He also landed on virtually inaccessible Peter the First Island. Here he collected a skua, and a Chinstrap penguin, both of which he later had stuffed. He also took home a female sled dog, who back in Washington gave birth to 16 pups. As a result of his work with aerial photographs he named several glacial ice floes. Roscoe also visited Little America, now covered with ice since the previous expedition, Operation Highjump. The rows of tents and the R4D aircraft were all buried in ice. One aircraft engine was dug out and it worked fine. Also a Weasel vehicle was chipped out of the ice and it also ran well. Once Operation Windmill concluded, Roscoe returned to duty with the Navy in Washington, D.C., and worked to assemble a bibliography on Antarctica that later was published. It categorized every expedition separately, including the old ones. As Operation Deepfreeze was being planned by Byrd and others, Roscoe, a civilian, was assigned by the Navy to work with Byrd. By then Roscoe and Byrd had developed a close working relationship. Byrd was a principal advisor in planning for the International Geophysical Year (IGY) in 1956-57. He returned to Antarctica in Deepfreeze I, but Roscoe did not, although he served as Byrd’s scientific and international affairs advisor. He made all the arrangements for the interchanges of people to send to foreign expeditions. In Washington he worked closely with Harry Dater, and Vi Malcolm, the last Commanders of the WAVES. Their office in Washington was in the Executive Office Building, next to the Blair House, and across the street from the White House. On his final trip to Antarctica, Operation Deepfreeze I, Byrd was accompanied to Antarctica by Paul Siple. Roscoe remained in Washington to run the office. Byrd became ill while there, cut short his trip, and after his return home he died in April, 1957. Shortly before the death of Admiral Byrd, Roscoe resigned from Civil Service and accepted an attractive position with the Lockheed Corporation. He designed the photographic system for the first American satellite. The Russians had just launched their Sputnik satellite. Roscoe never returned to the polar regions. He recalled various ways his polar experiences had affected his life. He found the Antarctic continent absolutely beautiful. It went beyond “black and white” colors since there were many shades of white, all of which Roscoe had learned to interpret as he studied aerial photographs. He also had become acutely aware of the dangers of the continent. He used the data he gathered there to earn his doctorate from the University of Maryland in 1952. His six-volume dissertation was on the morphology of the Antarctic continent. He used Operation Highjump photographs plus some others. He also edited a 5000-entry bibliography on the Antarctic in 16 languages. Roscoe also served as Vice President of the American Polar Society from 1957 until (at least) 2002 (the date of this interview). Roscoe continued to add to his impressive polar library, and suggested that he might be willing to donate it to the Byrd Polar Research Center. He suggested names from time to time for Antarctic features. He cooperated with publishers of such projects as Burrell’s Board of Place Names and Geographic Names of the Antarctic. He served on the Board of the Polar Times, and occasionally contributed to an article. A glacier was named for Roscoe. Since his retirement from Lockheed in 1982, Roscoe has developed an interest in history, and has done much reading and some research on the Crusades and the Knights Templar. He has also been an active member of the Masons. Major Topics Details about Operations Highjump, Windmill, and Deepfreeze in Antarctica Role of Admiral Richard Byrd in Antarctic explorations Pioneering role of Roscoe in interpreting aerial photography in Antarctica Personal and professional challenges in Antarctic exploration Contributions of various participants in Antarctic exploration Roscoe’s post-polar career at Lockheed and elsewhere Funded by a grant from the National Science Foundation.